PEMAHAMAN USTADZ YUSUF MANSUR TENTANG KONSEP ‘KUN FA YAKUUN’ DALAM QS. YASIN : 82 - Irfan Afandi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2015)
The interpretation of the holy Al-Qur’an find many varieties and perspective. This makes the Qur’an remains can be guidance for mankind. The future, the fate and safety human in the face of an uncertain future and tend to move out of the planing-planning man-made. From problem understanding : Yusuf Mansur on the concept kun fa yakuun get relevance. Kun fa fakuun is a manifestation of omnipotence Allah SWT where if wills will happen. Humans can beg and ask to face the problems that it faces. Surely there are steps which must be done. There are five (5) concepts offered by Yusuf Mansur as the answer to the problems of modern man to g et kun fa yakuun or help of Allah namely, the concept of monotheism, the concept of repentance, the concept of submission (trust), the mathematical alms and praying. In the hermeneutical dimension / comprehension passages al-Quran regarding the intent concept yakuun fa, YM present verses supporting inter-paragraph which is absurd. YM also prove that the verses of the al-Quran each other interpret and explain. While the aesthetic dimension YM present hu- man experiences when have practiced five concepts that he offers. As mathematics alms will not reduce proper- ty human but rather adds. As well, the experience of teachers TK wanting payrolls rose by tahajud and establish prayer alms. In essence, what is done by humans to perform five steps to achieve kun fa yakuun or getting help is the means / tools communication between god and man.